Trade Wind Boundary Layer Turbulence and Shallow Precipitating Convection: New Insights Combining SAR Images, Satellite Brightness Temperature, and Airborne In Situ Measurements - P.‐E. Brilouet; D. Bouniol; F. Couvreux; A. Ayet; C. Granero‐Belinchon; M. Lothon; A. Mouche (Geophysical Research Letters, 2023)
Abstract The imprint of marine atmospheric boundary layer (MABL) dynamical structures on sea surface roughness, as seen from Sentinel‐1 synthetic aperture radar (SAR) acquisitions, is investigated. We focus on 13 February 2020, a case study of the elucidating the role of clouds‐circulation coupling in climate field campaign. For suppressed conditions, convective rolls imprint on sea surface roughness is confirmed through the intercomparison with MABL turbulent organization deduced from airborne measurements. A discretization of the SAR wide swath into 25 × 25 km2 tiles then allows us to capture the spatial variability of the turbulence organization varying from rolls to cells. Second, we objectively detect cold pools within the SAR image and combine them with geostationary brightness temperature. The geometrical or physically‐based metrics of cold pools are correlated to cloud properties. This provides a promising methodology to analyze the dynamics of convective systems as seen from below and above.